Understanding Talent Retention within a Sport System: Exploring the Elite Youth Hockey Development System in Alberta, Canada - Jonathon Edwards (Journal of Applied Sports Management, 2016)
The study examines the regulations and strategies implemented by management of club hockey organizations and governing hockey bodies in the Edmonton region of Alberta, Canada to retain their talented youth athletes. Interviews were conducted with 13 representatives of six club hockey organizations and three governing bodies. The findings revealed that Residential Boundary regulations, Player Development, Facility Ownership, Performance Driven Outcomes, and Information Sharing comprised the system, and were used as a means of retaining youth elite athletes at key transition points. It was determined that management of club hockey organizations operate within a closed sport system, and based on this closed system, management implements regulations and strategies to effectively retain elite-level hockey players.
Keywords: athlete retention; sport systems; retention regulations; retention strategies; athlete pathways; hockey